Moffat's trusts law text and materials - Garton, Jonathan; Probert, Rebecca 1973-; Bean, Gerard M. D. (Cambridge University Press, 2020)
"A 'trust' in English law is in some measure the translation into legal terms of the word 'trust' as used in ordinary speech. Its conceptual starting point is 'a confidence reposed in some other' (this phrase is from the sixteenth-century legal commentaries of Lord Chief Justice Coke). The 'confidence' so reposed gives rise to moral obligations to which the courts, aided by the legislature, have purported to develop legal parallels. Inevitably, the moral weight given to trust and trusteeship in ordinary usage - to be 'in breach' of a 'sacred trust' is a serious matter, with repercussions possibly in the next world as well as this one - has had a significant impact on both the scope and the content of trusts law principles. There are still some contexts in which it may be difficult to say whether the word 'trust' is used in a legal or purely moral sense"--
Includes bibliographical references and index
Keywords: Trusts and trustees / England